A Mixed-Methods Study of How a Critical Race Theory-Informed Undergraduate Research Experience Program Provides Equitable Support for Aspiring Graduate Students - Frank Fernandez; Sarah Mason; Shannon Sharp; Gabriela Chavira; Crist S. Khachikian; Patchareeya Kwan; Carrie Saetermoe (MDPI AG, 2024)
Numerous studies document the benefits of participating in undergraduate research experiences (UREs), including greater odds of enrolling in graduate school. However, there is a lack of understanding about how UREs support student success. This study examines survey and interview data from a multi-year program evaluation of a National Institutes of Health-funded biomedical training program to consider whether and how participating in a URE fosters students' sense of belonging, which is an important predictor of retention and graduation. Analyzing the quantitative survey data revealed that participating in the URE was positively associated with a sense of belonging even after controlling for students' background characteristics, including gender, race or ethnicity, first-generation status, commuting burden, and age. Additionally, there was a positive relationship between a sense of belonging and odds of applying to graduate school. Path analysis suggests that the URE has an indirect relationship with applying to a graduate program that operates through the URE's direct relationship with sense of belonging. Interview data offered insights into how the URE supported an increased sense of belonging. Specifically, we found that the URE fostered a sense of belonging when (1) faculty research mentors develop authentic, personal, and caring relationships with mentees, (2) the URE program welcomes, cultivates, and supports women and racially diverse students, and (3) the URE is embedded within a university environment that allows for faculty and peer engagement.